Case report: A rare case of TBL1XR1-RARB positive acute promyelocytic leukemia in child and review of the literature - Jiang, Mingyan; Li, Jinrong; Wu, Jianrong; Zhu, Yiping; Gao, Ju (Frontiers in Oncology, 2022)
Some forms of acute myelogenous leukemia (AML) share typical morphological and immunophenotypic features of acute promyelocytic leukemia (APL) but are negative for promyelocytic leukemia-retinoic acid receptor alpha (PML-RARA) fusion. These forms of AML are known as variant APL. Some variants of APL present with retinoic acid receptor beta (RARB) fused or rearranged with partner genes. RARB-positive APL is very rare, resistant to all-trans retinoic acid (ATRA), and associated with poor prognosis. Here, we reported one case with TBL1XR1-RARB positive APL, featured by early onset and no apparent bleeding tendency or coagulation dysfunction. This patient was resistant to ATRA and arsenic trioxide (ATO), but was good responsive to conventional chemotherapy for AML. The case report was followed by a literature review.